Nexus between corporate social responsibility disclosure and stock returns of Russian firms - Orazayeva, A.; Arslan, M. (Journal of Economic Research & Business Administration, 2021)
Purpose: The objective of this study is to assess whether the quality of sustainability disclosure has any effect on the stock returns of Russian firms. Methodology: This study collects data from the 140 annual and sustainability reports of 23 Russian firms for the period 2013-2019. The study estimates corporate social responsibility (CSR) score based on the content analysis of the reports on the following dimensions: community contribution, environmental impact, employee relations, and provision of social products and services. Descriptive statistics, correlation analysis, and ordinary least squared regression were used to examine the nexus between CSR score and stock returns. Findings: No statically significant relationship was observed between CSR disclosure and stock returns of Russian firms. Though, the study documented a tremendous increase in the volume, as well as the quality of CSR disclosures over the sample period. This finding suggests that Russian firms are driven by other reasons for improving disclosure of sustainability practices other than variation in stock prices. The study also reports a statistically significant relationship of CSR disclosure with other variables utilized in the model, particularly total assets, return on assets (ROA), and leverage. Practical Implications: The study has several practical and theoretical implications. The findings of the study motivate the managers to improve the content of disclosed information, and for policymakers by providing criteria to assess the completeness and quality of disclosures, thereby indirectly enchasing more CSR initiatives and bringing social good. Originality/value: The study pictures the evolvement of CSR disclosures over the most recent sevenyear period, including the years of the increased popularity of sustainability practices. Russian market presents an interesting case for the research of CSR due to its post-communist background which shaped a unique set of societal values. The study extends and contributes to prior literature in understanding the evolvement of the role of CSR for Russian firms. Key words: CSR, environment, society, community, contribution, stock returns.